Cover Picture: A Practical One‐Pot Synthesis of Positron Emission Tomography (PET) Tracers via Nickel‐Mediated Radiofluorination (ChemistryOpen 4/2015) - Zlatopolskiy, Boris D.; Zischler, Johannes; Urusova, Elizaveta A.; Endepols, Heike; Kordys, Elena; Frauendorf, Holm; Mottaghy, Felix M.; Neumaier, Bernd (ChemistryOpen (Weinheim), 2015)
The cover picture shows the differences in brain metabolism of a healthy young and a healthy old subject, as well as a patient suffering from Parkinsons disease (left to right) uncovered by 6‐[18F]FDOPA‐positron emission tomography (PET). Morbus Parkinson occurs when nerve cells that produce dopamine begin to die. The shortage of dopamine leads to movement problems in affected individuals. 6‐[18F]FDOPA is extensively used to evaluate the progression of Parkinsons disease. Bold stick projections of this PET tracer, as well as a neuronal network, are seen in the background. Unfortunately, conventional procedures to produce 6‐[18F]FDOPA are cumbersome. Thus, several recent developments aim at the simplification of this radiosynthesis. In our work, we studied the applicability of the recently reported Ni‐mediated radiofluorination approach for daily routine production of 6‐[18F]FDOPA. For more details, see the Full Paper on p. 457 ff.